Effect of boron addition on microstructure, mechanical properties and oxidation resistance of TaC ceramics. Issue 6 (15th April 2019) - Lu, Zhuang; Liu, Limeng; Geng, Guihong; Laptev, Alexander M.; Hou, Zhaoping; Wang, Yujin
Abstract: TaC ceramics with 0.03–0.60 wt% of boron additions were prepared by hot pressing at 2100 °C for 1 h under a pressure of 40 MPa. Effects of boron content on densification, phase composition, microstructure, mechanical properties and oxidation resistance of the TaC ceramics were investigated. When the boron content was 0.12 wt% and above, full density was obtained due to reactions between boron and oxygen impurity at presence of TaC. Minor phases of TaB2 and C were formed in the 0.24 and 0.60 wt% B compositions after gas-out of the oxygen impurity. Microstructure of the TaC ceramics was refined with increasing in boron content. The TaC ceramic with 0.24 wt% of boron showed the best mechanical properties with a Vickers hardness, flexural strength and fracture toughness of 17.7 GPa, 534 MPa and 4.6 MPa m 1/2, respectively. When more boron was added, interfacial bonding of the TaC grains was strengthened causing a decrease in fracture toughness. Oxidation resistance of the TaC ceramics increased with boron content. Particularly, the 0.60 wt% B composition showed a weight gain of 0.0018 g/cm 2 after oxidization at 800 °C in air for 3 h.